Psychosocial volunteer support for older adults with cognitive impairment: development of MyCare Ageing using a codesign approach via action research. Issue 9 (29th September 2020) - Ayton, Darshini; O'Donnell, Renée; Vicary, Dave; Bateman, Catherine; Moran, Chris; Srikanth, Velandai K; Lustig, Julie; Banaszak-Holl, Jane; Hunter, Peter; Pritchard, Elizabeth; Morris, Heather; Savaglio, Melissa; et al.
Abstract : Background and objectives: Older adults with cognitive impairment are vulnerable to frequent hospital admissions and emergency department presentations. The aim of this study was to use a codesign approach to develop MyCare Ageing, a programme that will train volunteers to provide psychosocial support to older people with dementia and/or delirium in hospital and at home when discharged from hospital. Setting: Melbourne, Victoria, Australia. Research design: This study adopts an action research methodology. We report on two co-design workshops with keystakeholders: Workshop 1: identification of components from three existing programmes to inform the development of the MyCare Ageing program logic and, Workshop 2: identification of implementation strategies. Participants: The key stakeholders and workshop participants included clinicians (geriatricians, nurses and allied health), hospital staff (volunteer coordinators and hospital executives), Baptcare staff, a consumer, researchers and implementation experts and project staff. Results: Workshop 1 identified the components from three existing programmes—the Volunteer Dementia and Delirium Care programme, Home-Start and MyCare for inclusion in MyCare Ageing. In workshop 2, the p implementation plan was developed taking into consideration hospital-specific processes, training and support needs of volunteers and safety and risk management processes. Discussion and conclusion: The codesign process was successfully applied to develop the MyCare Ageing programme to provide volunteer support to patients with dementia and/or delirium in hospital and their transition home. MyCare Ageing is an innovative programme that meets an identified need from hospitals and consumers to support patients with dementia and/or delirium to improve psychosocial outcomes on discharge from hospital.